Penile Self-amputation - Manganiello, Marc Damian; Knaus, William J.; Cohen, Justin B.; Lee, Bernard T. (Journal of Reconstructive Microsurgery Open, 2017)
Background A 24-year-old man was urgently transferred from an outside institution after self-amputating his penis.Methods The patient was suffering from a paranoid schizophrenic delusional episode. Voices told him to amputate his own penis with a utility knife. He was taken emergently to the operating room by urology and plastic surgery. Cystoscopy was performed and a 14F percutaneous suprapubic catheter was placed. The amputated distal penis and the proximal stump were debrided. The urethra, dorsal artery, and neurovascular bundles were mobilized. The distal urethra was spatulated dorsally and the proximal urethra was spatulated ventrally. The urethra was reanastomosed over a 16F Foley catheter with interrupted, 4–0 absorbable, monofilament suture. The corpora were reanastomosed with interrupted, 2–0 and 3–0, absorbable, monofilament suture. The arteries and nerve were reanastomosed. Total ischemia time was between 4 and 5 hours.Results The patient initially developed edema, ecchymosis, and mild incisional skin necrosis from the resulting reperfusion injury. However, the penile graft successfully maintained perfusion. He was discharged 2 weeks after his injury in stable psychiatric condition. His Foley catheter and suprapubic tube remained in place for 10 weeks. A voiding cystourethrogram (VCUG) demonstrated a patent urethra without evidence of urinary leakage or stricture. At the time of his VCUG, he experienced return of distal penile sensation and partial erections.Conclusion Penile reimplantation after self-amputation is successful if ischemic time is minimized and a multidisciplinary approach with plastic surgery and microvascular anastomosis is performed.
Keywords: penile amputation; microvascular anastomosis